TINJAUAN YURIDIS PELAKSANAAN LELANG EKSEKUSI HAK TANGGUNGAN TERHADAP DEBITUR WANPRESTASI BERDASARKAN UNDANG-UNDANG NOMOR 4 TAHUN 1996 TENTANG HAK TANGGUNGAN DAN PERATURAN MENTERI KEUANGAN NOMOR 122/PMK.06/2023 - Irwan Sapta Putra; Mohammad Hifni; Siti Faozah (Gapenas Publisher, 2026)
The execution auction of Mortgage Rights is one of the legal mechanisms for resolving non-performing loans by granting creditors the authority to obtain repayment of their receivables through the sale of mortgaged property when the debtor is in default. The legal framework governing the implementation of Mortgage Right execution auctions is stipulated in Law Number 4 of 1996 concerning Mortgage Rights and Minister of Finance Regulation Number 122/PMK.06/2023 concerning Guidelines for Auction Implementation. However, in practice, there are still differing interpretations regarding the implementation of parate executie, potential inconsistencies among statutory regulations, and variations in judicial decisions, which affect legal certainty and legal protection for creditors, debtors, and auction purchasers. This study aims to analyze the legal regulations governing the implementation of Mortgage Right execution auctions against defaulting debtors based on the applicable laws and regulations, as well as to examine whether their implementation reflects the principles of legal certainty, justice, and legal protection. This research employs a normative legal research method using the statutory approach, conceptual approach, and case approach. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively through library research. The findings indicate that the legal framework governing Mortgage Right execution auctions has been adequately established under the Indonesian Civil Code, Law Number 4 of 1996 concerning Mortgage Rights, Law Number 10 of 1998 concerning Banking, and Minister of Finance Regulation Number 122/PMK.06/2023 concerning Guidelines for Auction Implementation. Nevertheless, differing interpretations of Articles 6 and 20 of the Mortgage Rights Law regarding the implementation of parate executie continue to hinder the realization of optimal legal certainty in practice. Therefore, harmonization of statutory regulations and consistent law enforcement are necessary to ensure legal certainty, justice, and balanced legal protection for creditors, debtors, and auction purchasers.